PENURUNAN KECEMASAN BERBICARA DI DEPAN KELAS MELALUI BERPIDATO PADA SISWA KELAS XI MIA 3 MAN 2 MODEL PEKANBARU - Lastri Erman; Rosmawati '; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this study was the number of students who did not dare to appear and speak in front of the class when it comes to perform various activities that require speaking in front of people like presentation, speech, and speech. The study also aims to reduce anxiety speak to the class to students through speech techniques. The method in this research is action counseling carried out in two cycles. with qualitative data analysis techniques. and the subjects in the study were students of class XI MIA 3 MAN 2 Model Pekanbaru amounting to 23 students. With research procedures and discussion shows the results of the first cycle there are six (21%) of students are at very high category, 12 (43%) of students at the high category, 9 (32%) of students are in the low category, and 1 (4% ) students are at very low category. In Cycle II results showed that there is a decrease in the level of anxiety to speak to the class experienced by students that there are two (7%) of students who are at very high category, seven (25%) of students at the high category, 15 (54%) students are in the low category, and 4 (14%) of students who are in the very low category. This shows that the speech exercises can reduce the level of anxiety to speak to the class.Key Words: anxiety to speak in front of class